The subepidermal moisture scanner: the technology explained. (1st February 2020) - Gefen, Amit; Ross, Graham
Abstract : The objective of this article is to explain the biophysical principles underlying the design of the subepidermal moisture (SEM) scanner, commercially known as the 'SEM scanner'. We also describe the mode of operation of the SEM scanner in monitoring tissue health and detecting subtle abnormal changes in tissue physiology in patients and anatomical sites at a risk of a pressure ulcer (PU: also known as a pressure injury). The technology of the SEM scanner was approved last year for sales in the US by the Food and Drug Administration (FDA). The SEM scanner detects changes in fluid contents of human skin and subdermal tissues, to a tissue depth of several millimetres, by measuring 'capacitance', an electrical property of the locally examined tissue site to store electric charge. The capacitance of tissues, called 'biocapacitance', is strongly affected by the amount of fluid (water) in the tissue. When the first cells die in a forming PU, inflammatory signalling causes the permeability of blood vessel walls to increase and oedema to develop. Simply, the scanner detects the early appearance of oedema, which is called 'micro-oedema.' Calculation of a 'SEM-delta' value, which compares biocapacitance measurements, acquired across several tissue sites, some of which are healthy and others where the PU may evolve, eliminates potential effects of systemic changes in tissue fluid contents and provides a consistent quantitative measure of the tissue health conditions at the monitored anatomical site. Here, we describe SEM scanner technology, how it operates and has been laboratory tested (in computer simulations, in silico ) before commercial launch. We explain why targeting the physical biomarker of oedema leads to the documented success of the SEM scanner in the multiple published clinical trials, proving its ability to early detect PUs that form under intact skin.